Embedded vision : an introduction - Vijayalakshmi, S. R. (Mercury Learning and Information, 2020)
An introductory guide for anyone who is interested in designing machines that have vision-enabled, embedded products, this book covers topics encountered in hardware architecture, software algorithms, applications, advancements in processors and sensors. --